Pendampingan UMKM Berbasis Potensi Lokal: Strategi Meningkatkan Daya Saing di Desa Pesisir Besuki - Moh Rasidi; Syafiul Anam; Ubaidillah; Muhammad Rizal Ubaidillah; Rizki Alif Ramdhani; Zainul Qudsi; Samsul Arifin (Yayasan Literasi Altruis Khatulistiwa, 2025)
Micro, Small, and Medium Enterprises (MSMEs) producing fish crackers in Pesisir Village, Besuki District, face several challenges, particularly limited access to computer technology and digital marketing skills. Despite having strong local potential, these MSMEs struggle to promote their products effectively and expand their market reach. This community service program aims to provide assistance based on local potential to enhance the competitiveness of these businesses sustainably. The activities include training in digital marketing strategies, mentoring in the creation of promotional content such as short video reels and digital posters, and facilitating the development of sales networks in regions where the PKM team members reside. The solutions offered are practical and tailored to meet the real needs of MSMEs in improving promotion and efficiency. Preliminary results show an increase in participants’ ability to produce marketing content and the identification of potential distribution partners in several areas. Through a local-potential-based approach and digital technology support, this program is expected to improve the competitiveness, market reach, and ultimately the income of fish cracker MSMEs in a sustainable manner.